Banquet Hall Organizer: Efficient Banquet Hall Booking and Admin Control - Patil, Maheshwari; Lande, Sayali; Raut, Shweta; Jamadade, Pranjali; Kamble, Aishwarya (International Journal of Computer Sciences and Engineering, 2024)
The Banquet Hall Management System (BHMS) is a powerful software solution tailored to optimize the day-to-day operations of banquet hall management. It provides a range of features designed to help administrators efficiently manage event bookings, resources, and customer interactions. With real-time availability tracking, the system ensures that administrators and clients alike have up-to-date information on hall schedules and availability, eliminating double bookings and allowing for more effective resource management. One of the standout features of BHMS is its integrated customer relationship management (CRM) functionality, which enables personalized service and streamlined communication with clients. This improves customer satisfaction by ensuring their specific needs are met. The system also automates billing and invoicing processes, reducing the likelihood of errors and significantly cutting down administrative workload. The BHMS is equipped with a user-friendly interface that includes an integrated scheduling calendar, making it easy for staff to manage multiple events simultaneously. This not only enhances operational efficiency but also facilitates better planning and coordination. By providing an all-in-one solution for event booking, resource management, customer engagement, and automated billing, the BHMS plays a crucial role in elevating the professionalism and efficiency of banquet hall operations, making it an indispensable tool for modern venues.